The Effect Of Smash Training With The Drill Smash Method On Accuracy Of Badminton Smash At UPTD Elementary School Lombang Dajah 1 Blega - Trio Gatra; Heni Yuli Handayani; Khoirul Anwar (UNIVERSITAS NEGERI MAKASSAR, 2022)
This type of research data is quasi-experimental using quantitative methods. The sampling technique is quota sampling which is included in the non-probability sampling. The research data collection used a badminton smash accuracy test through pretest and post-test. The data analysis technique used descriptive analysis. The results of this study from the two hypotheses tested indicate that there is an effect of smash training with the drill smash method on the accuracy of badminton and smash. Based on the results of the t-test in the form of a paired sample test, it shows that the significant value is 0.000, meaning less than 0.05, and then H0 is rejected. This shows that the results of providing learning before and after using the exercise method are not the same, thus it can be said that there is a significant difference between before and after giving the exercise to students.